Aspirations and expectations towards studying of students and listeners of the University of the Third Age and the attitude of „to have” and „to be” - Monika Czerw; Elena Karpuszenko; Daniel Kukla (Edukacja Ustawiczna Dorosłych)
The idea of lifelong education is quite widely promoted in our society, among other things pursued by adult citizens. Therefore, the educational and personal aspirations of adults and their expectations of studying were the subject of the study. Students took part in the research. However, they were not students starting their studies immediately after graduating from secondary school, but persons who undertook their studies already during their professional career – they came to study as part-time or postgraduate students. The second group was made up of students of the University of the Third Age. The study additionally took into account the motives for studying and the accompanying “to have” or “to be” attitude. This is because it was assumed that the more personal and educational aspirations are satisfied while studying, the more often the respondents will present a “to be” attitude.